MAINTAINING NARRATIVE CONSISTENCY AND BRAND IDENTITY ON WEBSITES, SOCIAL MEDIA, EMAIL, AND MARKETPLACES: A SYSTEMATIC LITERATURE REVIEW FOR BUILDING TRUST AND BRAND RECOGNITION - Axelon S Renyaan; Tehedi Tehedi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to examine the importance of narrative consistency and brand identity across various digital channels, particularly websites, social media, email, and marketplaces, in building consumer trust and increasing brand recognition. Through a systematic literature review approach, this study analyses the relationship between brand communication consistency and two strategic elements, namely consumer trust and brand recognition. The results show that consistent narratives prevent message contradictions, strengthen perceptions of brand authenticity and credibility, and increase consumer loyalty. Meanwhile, consistent visual and verbal identities have been proven to accelerate brand recognition, build strong associations, and create sustainable differentiation in a competitive market. In practical terms, this study emphasises the importance of developing comprehensive brand guidelines and implementing integrated cross-channel communication strategies to deliver a harmonious brand experience. These findings not only enrich the academic literature on branding in the digital context but also have real implications for companies seeking to build sustainable competitive advantage in the digital age.